2018
DOI: 10.1021/acs.jmedchem.8b00790
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structure–Activity Relationships Study of Odilorhabdins, a New Class of Peptides Showing Potent Antibacterial Activity

Abstract: The spread of antibiotic-resistant pathogens is a growing concern, and new families of antibacterials are desperately needed. Odilorhabdins are a new class of antibacterial compounds that bind to the bacterial ribosome and kill bacteria through inhibition of the translation. NOSO-95C, one of the first member of this family, was synthesized for the first time, and then a structure-activity relationships study was performed to understand which groups are important for antibacterial activity and for inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Among them, carbapenem‐resistant Enterobacteriaceae (CRE) has aroused great concern due to its rapid dissemination and high mortality rates . Carbapenemases, such as New Delhi metallo‐β‐lactamase‐1 (NDM‐1), produced by these strains are considered to result in the neutralization and thus ineffectiveness of β‐lactam antibiotics through hydrolysis . Moreover, cross‐resistance is becoming increasingly serious.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, carbapenem‐resistant Enterobacteriaceae (CRE) has aroused great concern due to its rapid dissemination and high mortality rates . Carbapenemases, such as New Delhi metallo‐β‐lactamase‐1 (NDM‐1), produced by these strains are considered to result in the neutralization and thus ineffectiveness of β‐lactam antibiotics through hydrolysis . Moreover, cross‐resistance is becoming increasingly serious.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Carbapenemases, such as New Delhi metallo-b-lactamase-1 (NDM-1), produced by these strains are considered to result in the neutralization and thus ineffectiveness of b-lactam antibiotics through hydrolysis. [3] Moreover,c ross-resistance is becoming increasingly serious. Bacteria have evolvedv arious ways to defend against frequently used antibiotics, such as daptomycin and vancomycin.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the non-standard amino acids, Dab(βOH) and Dha, were not commercially available and were required for the total synthesis of NOSO-95C. We developed their synthesis on a multi-gram scale and reported the first total synthesis of NOSO-95C (Sarciaux et al, 2018). The 1 H NMR and LC-MS spectra and antibacterial activity of the natural and synthetic peptides were similar.…”
Section: Structural Determination and Identification Of The Biosynthementioning
confidence: 99%
“…Based on these encouraging results and with a validated synthetic method, we initiated a medicinal chemistry program on NOSO-95C to study the structure-activity relationships (SAR) of ODLs with the objective to better understand the role of each amino acid for the antibacterial activity and the inhibition of bacterial translation (Sarciaux et al, 2018). Before starting this study, the inhibition of bacterial translation was identified as the principal mode of action of ODLs.…”
Section: Structure-activity Relationships and Selection Of A Preclinimentioning
confidence: 99%
See 1 more Smart Citation